Vaccination and Infection of Swine With Salmonella Typhimurium Induces a Systemic and Local Multifunctional CD4+ T-Cell Response - Schmidt, Selma; Sassu, Elena L.; Vatzia, Eleni; Pierron, Alix; Lagler, Julia; Mair, Kerstin H.; Stadler, Maria; Knecht, Christian; Spergser, Joachim; Dolezal, Marlies; Springer, Sven; Theuß, Tobias; et al. (Frontiers in Immunology, 2021)
The gram-negative facultative intracellular bacteria Salmonella Typhimurium (STM) often leads to subclinical infections in pigs, but can also cause severe enterocolitis in this species. Due to its high zoonotic potential, the pathogen is likewise dangerous for humans. Vaccination with a live attenuated STM strain (Salmoporc) is regarded as an effective method to control STM infections in affected pig herds. However, information on the cellular immune response of swine against STM is still scarce. In this study, we investigated the T-cell immune response in pigs that were vaccinated twice with Salmoporc followed by a challenge infection with a virulent STM strain. Blood- and organ-derived lymphocytes (spleen, tonsils, jejunal and ileocolic lymph nodes, jejunum, ileum) were stimulated in vitro with heat-inactivated STM. Subsequently, CD4+ T cells present in these cell preparations were analyzed for the production of IFN-γ, TNF-α and IL-17A by flow cytometry and Boolean gating. Highest frequencies of STM-specific cytokine-producing CD4+ T cells were found in lamina propria lymphocytes of jejunum and ileum. Significant differences of the relative abundance of cytokine-producing phenotypes between control group and vaccinated + infected animals were detected in most organs, but dominated in gut and lymph node-residing CD4+ T cells. IL-17A producing CD4+ T cells dominated in gut and gut-draining lymph nodes, whereas IFN-γ/TNF-α co-producing CD4+ T cells were present in all locations. Additionally, the majority of cytokine-producing CD4+ T cells had a CD8α+CD27- phenotype, indicative of a late effector or effector memory stage of differentiation. In summary, we show that Salmonella-specific multifunctional CD4+ T cells exist in vaccinated and infected pigs, dominate in the gut and most likely contribute to protective immunity against STM in the pig.